Segmental Testicular Infarction, an Underdiagnosed Entity: Case Report with Histopathologic Correlation and Review of the Diagnostic Features - Sahar Shiraj; Nisha Ramani; Andrij R. Wojtowycz (Case Reports in Radiology)
A 30-year-old male presented with a 1-day history of left scrotal pain and a tender left testicle and epididymis on physical exam. Scrotal ultrasound showed an avascular, heterogeneous, hypoechoic lesion in the superior left testis suggestive of infarction or neoplasm. The patient was managed conservatively; however, his pain continued and follow-up ultrasound 6 days later showed interval increase in the size of the mass. Left radical orchiectomy was done and pathology result showed segmental infarction of the left testis.